2012
DOI: 10.1007/s00508-011-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Konsensusbericht Hämorrhoidalleiden

Abstract: Haemorrhoidal disease belongs to the most common benign disorders in the lower gastrointestinal tract. Treatment options comprise conservative as well as surgical therapy still being applied arbitrarily in accordance with the surgeon's expertise. The aim of this consensus statement was therefore to assess a stage-dependent approach for treatment of haemorrhoidal disease to derive evidence-based recommendations for clinical routine. The most common methods are discussed with respect of haemorrhoidal disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
1
0
0
Order By: Relevance
“…It has been estimated that 25% to 35% of pregnant women are affected by this condition. In certain populations, up to 85% of pregnancies are affected by hemorrhoids in the third trimester (Abramowitz et al,2012). Results indicated also that the presence of family history of disease among majority of the patients, accordance with Gaj and Trecca 2007 w,ho reported that, hemorrhoid causes could be attributed to a family history of "weak" veins that lead to the development of hemorrhoids and other varicose veins.…”
Section: Study Group N =50supporting
confidence: 75%
“…It has been estimated that 25% to 35% of pregnant women are affected by this condition. In certain populations, up to 85% of pregnancies are affected by hemorrhoids in the third trimester (Abramowitz et al,2012). Results indicated also that the presence of family history of disease among majority of the patients, accordance with Gaj and Trecca 2007 w,ho reported that, hemorrhoid causes could be attributed to a family history of "weak" veins that lead to the development of hemorrhoids and other varicose veins.…”
Section: Study Group N =50supporting
confidence: 75%